The Impact of Advantages and Comfort on Consumers' Desire to Continue Doing Business Online in E-Commerce - Sri Handayani (Journal of Social Science and Business Studies, 2024)
This research aims to examine the influence of benefits and convenience on interest in continuing online transactions. Research respondents were students from various universities in Surabaya who made online transactions in e-commerce. To test the proposed hypothesis, multiple regression analysis was used, with the independent variables benefit and convenience and the dependent variable interest in continuing online transactions. The research results show that benefits and convenience have proven to have a significant positive effect on interest in continuing online transactions in e-commerce. This shows that the greater the benefits of transacting in e-commerce, the greater the consumer's interest in continuing the transaction again, and the more comfortable the consumer is in carrying out transactions in e-commerce, the greater the consumer's interest in continuing the transaction again.